Genetic and biochemical studies in Argentinean patients with variegate porphyria - Giudice Jimena; Granata Bárbara X; Rossetti María V; Parera Victoria E; Batlle Alcira (BMC, 2008)
Abstract Background A partial deficiency in Protoporphyrinogen oxidase (PPOX) produces the mixed disorder Variegate Porphyria (VP), the second acute porphyria more frequent in Argentina. Identification of patients with an overt VP is absolutely important because treatment depends on an accurate diagnosis but more critical is the identification of asymptomatic relatives to avoid acute attacks which may progress to death. Methods We have studied at molecular level 18 new Argentinean patients biochemically diagnosed as VP. PPOX gene was amplified in one or in twelve PCR reactions. All coding exons, flanking intronic and promoter regions were manual or automatically sequenced. For RT-PCR studies RNA was retrotranscripted, amplified and sequenced. PPOX activity in those families carrying a new and uncharacterized mutation was performed. Results All affected individuals harboured mutations in heterozygous state. Nine novel mutations and 3 already reported mutations were identified. Six of the novel mutations were single nucleotide substitutions, 2 were small deletions and one a small insertion. Three single nucleotide substitutions and the insertion were at exon-intron boundaries. Two of the single nucleotide substitutions, c.471G>A and c.807G>A and the insertion (c.388+3insT) were close to the splice donor sites in exons 5, 7 and intron 4 respectively. The other single nucleotide substitution was a transversion in the last base of intron 7, g.3912G>C (c.808-1G>C) so altering the consensus acceptor splice site. However, only in the first case the abnormal band showing the skipping of exon 5 was detected. The other single nucleotide substitutions were transversions: c.101A>T, c.995G>C and c.670 T>G that result in p.E34V, p.G332A and W224G aminoacid substitutions in exons 3, 10 and 7 respectively. Activity measurements indicate that these mutations reduced about 50% PPOX activity and also that they co-segregate with this reduced activity value. Two frameshift mutations, c.133delT and c.925delA, were detected in exons 3 and 9 respectively. The first leads to an early termination signal 22 codons downstream (p.S45fsX67) and the second leads to a stop codon 5 codons downstream (p.I309fsX314). One reported mutation was a missense mutation (p.G232R) and 2 were frameshift mutations: c.1082insC and 1043insT. The last mutation was detected in six new apparently unrelated Argentinean families. Conclusion Molecular analysis in available family members revealed 14 individuals who were silent carriers of VP. Molecular techniques represent the most accurate approach to identify unaffected carriers and to provide accurate genetic counselling for asymptomatic individuals. The initial screening includes the insertion search.